The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.15760/etd.511
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence During the Transition from Prison to the Community: An Ecological Analysis

Abstract: While extensive research has been conducted on the causes of intimate partner violence in the community, very little is known about rates and predictors of domestic violence perpetrated by offenders who have recently been incarcerated. Some evidence suggests that formerly incarcerated individuals may be at an increased risk to perpetrate intimate partner violence during the transition from prison to the community (e.g., Hairston & Oliver 2006;Hilton, Harris, Popham, & Lang, 2010;Oliver & Hairston, 2008). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 272 publications
(328 reference statements)
0
4
0
Order By: Relevance
“…Approximately one quarter of men (26%) and women (24.7%) reported physical violence during the time between the male partner’s release and the first postrelease follow-up interview—a median time of 6 months. Freeland Braun (2012) found a similar prevalence of reentering men (25%) were suspected or taken into custody for a new domestic violence incident, with a much longer follow-up period (average of 4.4 years). Using a shorter time frame, within the last month, Grieb and colleagues (2014) revealed that 11% of respondents experienced physical altercations with an incarcerated family member.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…Approximately one quarter of men (26%) and women (24.7%) reported physical violence during the time between the male partner’s release and the first postrelease follow-up interview—a median time of 6 months. Freeland Braun (2012) found a similar prevalence of reentering men (25%) were suspected or taken into custody for a new domestic violence incident, with a much longer follow-up period (average of 4.4 years). Using a shorter time frame, within the last month, Grieb and colleagues (2014) revealed that 11% of respondents experienced physical altercations with an incarcerated family member.…”
Section: Resultsmentioning
confidence: 71%
“…Studies of samples who all experienced incarceration (Freeland Braun, 2012; McKay et al, 2018a; 2018b; Stansfield et al, 2020) all focused on incarcerated men (regardless of prior offense category) and testing whether the releasee perpetrated any new family violence, broadly defined. The one exception was a recent study by Mowen and Fisher (2019) that used a sample of juveniles within the Serious and Violent Offender Reentry Initiative (SVORI) data to examine new family violence incidents perpetrated by juveniles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations